2017
DOI: 10.1017/s0007114517002422
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency and insufficiency among schoolchildren in Greece: the role of sex, degree of urbanisation and seasonality

Abstract: The current study was aiming to report the prevalence of suboptimal vitamin D status among schoolchildren in Greece and investigate the role of sex, urbanisation and seasonality on vitamin D status. A sample of 2386 schoolchildren (9-13 years old) from four distinct prefectures was examined. The prevalence of 25-hydroxyvitamin D (25(OH)D) concentration <30 and <50 nmol/l (vitamin D deficiency and insufficiency respectively) was 5·2 and 52·5 %, respectively. Girls had a higher prevalence of 25(OH)D<30 (7·2 v. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
(68 reference statements)
12
29
1
7
Order By: Relevance
“…Authors have suggested different hypotheses such as the light‐dependent activity of the pineal gland and melatonin production (Weber et al, ), or seasonal differences in morbidity due to infectious diseases in tropical countries (Sohn, ). It is also worthy of note that in a recent study of the prevalence of vitamin D deficiency in Greece (Manios et al, ), the periods of the highest and lowest prevalence of hypovitaminosis D were essentially the same with the respective periods of lower and peak height observed in our study. This observation may lead to another hypothesis, namely, that either vitamin D is an important contributor of the early postnatal growth, as some authors have suggested (Roth, Perumal, Al Mahmud, & Baqui, ), or that both parameters are independently affected by the same condition, that is, solar radiation.…”
Section: Discussionsupporting
confidence: 88%
“…Authors have suggested different hypotheses such as the light‐dependent activity of the pineal gland and melatonin production (Weber et al, ), or seasonal differences in morbidity due to infectious diseases in tropical countries (Sohn, ). It is also worthy of note that in a recent study of the prevalence of vitamin D deficiency in Greece (Manios et al, ), the periods of the highest and lowest prevalence of hypovitaminosis D were essentially the same with the respective periods of lower and peak height observed in our study. This observation may lead to another hypothesis, namely, that either vitamin D is an important contributor of the early postnatal growth, as some authors have suggested (Roth, Perumal, Al Mahmud, & Baqui, ), or that both parameters are independently affected by the same condition, that is, solar radiation.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Mainos et al attributed most of the vitamin D deficiency prevalence in girls of 9 -13 years old in a city in Greece to an increase in indoor activities. Besides, some studies have attributed lower prevalence of vitamin D deficiency in men, despite having an equal BMI with women, to 10% -15% less body fat content, which leads to less amount of vitamin D stored in body fat and more amount of vitamin D available in blood (2,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The VDSP protocol for standardization of serum 25(OH)D values was applied to serum 25(OH)D data arising from previously analyzed serum samples using the chemiluminescence immunoassay analysis. The VDSP protocol and its application has been outlined in detail elsewhere, while more analytical information on the procedures followed for the standardization of serum 25(OH)D values in the present study has been recently provided elsewhere …”
Section: Methodsmentioning
confidence: 99%